Answer:
Step-by-step explanation:
<span>Here, Elaine = Tyler + (-8)
</span>⇒ E<span>laine + 0 + Tyler + 0 = 34
</span>⇒ T<span>yler + (-8) + 0 + Tyler + 0 = 34
And, Tyler = [(34 - (0) - (-8)] / 2
Thus, Tyler = 21
And, Elaine = 21 + (-8)
=13
</span>∴ T<span>yler = 21 & Elaine = 13
Regards
#Exotic Explorer</span>
Answer:![\frac{11}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B11%7D%7B-2%7D)
Step-by-step explanation:
ok so I'm going to try to show it the best c an
m = slope
the equation you use is
m
so when using that formula with the cords, you get
![\frac{4-(-7)}{-6-(-4)}](https://tex.z-dn.net/?f=%5Cfrac%7B4-%28-7%29%7D%7B-6-%28-4%29%7D)
and then subtract everything and you'll get
![\frac{11}{-2}](https://tex.z-dn.net/?f=%5Cfrac%7B11%7D%7B-2%7D)